2017
DOI: 10.1177/0963662517728478
|View full text |Cite
|
Sign up to set email alerts
|

Scientists’ views about communication objectives

Abstract: This study looks at how United States-based academic scientists from five professional scientific societies think about eight different communication objectives. The degree to which scientists say they would prioritize these objectives in the context of face-to-face public engagement is statistically predicted using the scientists' attitudes, normative beliefs, and efficacy beliefs, as well as demographics and past communication activity, training, and past thinking about the objectives. The data allow for que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 50 publications
7
114
1
2
Order By: Relevance
“…Both quantity and quality are important, but at some point, it may make more sense to think about how to recruit specific scientists to communicate and then focus on how to make these selected scientists effective. One useful thing to recognize about treating engagement behavior as planned behavior is that, while the current study focused on overall willingness to engage, similar models could be used to understand willingness to prioritize specific objectives (Besley, Dudo, & Yuan, 2017) or specific tactics. On tactics, an area that does not seem to have been studied, research might, for example, seek to assess what motivates participation in science cafés in comparison to more traditional public lectures or more elaborate deliberative events.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Both quantity and quality are important, but at some point, it may make more sense to think about how to recruit specific scientists to communicate and then focus on how to make these selected scientists effective. One useful thing to recognize about treating engagement behavior as planned behavior is that, while the current study focused on overall willingness to engage, similar models could be used to understand willingness to prioritize specific objectives (Besley, Dudo, & Yuan, 2017) or specific tactics. On tactics, an area that does not seem to have been studied, research might, for example, seek to assess what motivates participation in science cafés in comparison to more traditional public lectures or more elaborate deliberative events.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Unlike the establishment of codes of ethics that delineate the sanctions for laboratory work (Sharp, 2019), research institutes seldom mandate public engagement. Past studies have also found that the research fraternity stigmatized researchers who actively conducted public engagement, commonly known as the "Carl Sagan effect," deterring many researchers from conducting public engagement (Bauer and Jensen, 2011;Bentley and Skyvik, 2011;Besley et al, 2018aBesley et al, , 2018bDudo et al, 2018;Ecklund et al, 2012).…”
Section: Meso-level Considerationsmentioning
confidence: 99%
“…Indeed, outlining goals will help scientists identify a target audience, will guide the development of the content and approach of the communication, and will inform the development of assessment strategies. While an in‐depth discussion of “objectives” versus “goals” can be found elsewhere, herein goals are discussed with respect to a specific desired audience response or outcome irrespective of the timeline (Table ).…”
Section: Science Communication Goalsmentioning
confidence: 99%
“…Alongside an increasing appreciation of the importance of public understanding of STEM has been a call for scientists to become more involved in communicating science . Though many may be late to the game, there is currently an undeniably palpable and intensifying enthusiasm for science communication among practicing scientists . Many scientists, however, (me included) are struggling to determine their role in this growing field of science communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation